MEASUREMENT OF VERTICAL AND HORIZONTAL INTRA-INDUSTRY TRADE IN AGRICULTURAL FOOD PRODUCTS: THE CASE OF CHINA AND - Ercan ŞAHBUDAK (Fırat University, 2019)
In recent decades intra industry trade has become a widespread phenomenon with its growing role in international trade. Intra-industry trade is defined as the simultaneous export and import of products which belong to the same statistical product category. Intra industry trade has risen rapidly in the past three decades. Horizontal intra-industry trade is defined trade in similar products with differentiated varieties. Vertical intra-industry trade is defined trade products are distinguished by quality and price. The main object of this study is to examine the intra industry trade in agricultural food products of China and Brazil over 2000-2014. In order to calculate the intra-industry trade level of agricultural food products has used Grubel-Lloyd Index. Then, it calculated horizontal and vertical intra-industry trade. As a result of this study, it was found to be low the level of intra-industry trade in agricultural food products in China and Brazil. Also, it has seen low-quality vertical intra-industry trade in China and Brazil’s agricultural food products.